Analisis Pemahaman Masyarakat Desa Lam Ara Tunong terhadap Kesadaran akan Kepedulian Lingkungan - Phonna, Niea Zahara; Jayanti, Ummi Nur Afinni Dwi; Mardiah, Ros; Az-Zahra, Nabila (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The Lam Ara Tunong Village is located in a rural area with unique social and cultural characteristics. This analysis will examine the understanding of the people of Lam Ara Tunong Village regarding awareness and concern for the environment. The aim is to investigate the understanding and concern of the people of Lam Ara Tunong Village towards the environment, which is a key factor in maintaining ecosystem sustainability and natural balance. The research uses a survey method by distributing a Google form questionnaire to respondents. The research is expected to provide insights and open up the mindset of the people of Lam Ara Tunong Village. The population sampled is from Lam Ara Tunong Village, with a sample of 60 local residents. The data collection technique uses the Guttman scale, with the instrument of random sampling technique. Furthermore, the questionnaire data is analyzed by looking at the choice scores.